Pengaruh Tingkat Bunga, Nilai Kurs, Kebijakan Dividen, dan Inflasi terhadap Return Saham Perusahaan Perbankan: - Nyoman Kerameyuda; Gendro Wiyono; Ratih Kusumawardhani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Stock Return is the value obtained as a result of investment activities. The expected return is in the form of dividends for stock investments and interest income for investments. Return is the main goal of investors to get results from investments made by investors. Therefore, to be able to find out how much return will be obtained by investors, investors need to predict in order to find out how much return they will get. interest, exchange rate, dividend policy, and inflation on stock returns of banking companies on the IDX in 2016-2020. The sample in this study is 11 banking companies. Purposive sampling method is the method used to determine the sample of this research. The analytical method used is descriptive test, classical assumption test, and multiple regression analysis test using the SPSS application. The results of this study show that the interest rate and exchange rate variables have a positive effect, while dividend and inflation policies have a negative effect on stock returns. Keywords: the effect of interest rates, exchange rates, dividend policy, and stock inflation